Transition from traditional energy to renewable energy: assessment of the contribution of renewable energy in greenhouse gas emissions reduction on the example of the Yereimentau wind farm (Eurasian Journal of Ecology, 2022)
Kazakhstan has a high potential for creating international-class green energy, but at the moment alternative energy resources are used in a small amount due to various technical, administrative, social and economic obstacles. This work is devoted to the analysis of the share of renewable energy generated in the total volume of electricity production in Kazakhstan, the amount of electricity produced by renewable energy facilities is estimated. Also in this paper, an assessment of greenhouse gas emissions reductions was carried out on the example of the largest wind power plant in Kazakhstan with a capacity of 45 MW in the city of Yerementau. The share of renewable energy sources in the country’s energy balance was estimated by comparison. The annual data on the generation of electric energy by renewable energy facilities for 2016-2021 are compared according to the statistical data of the Republic of Kazakhstan. A methodological approach to the calculation of greenhouse gas emissions reductions based on a baseline scenario is proposed, which can be used as a methodology for calculating greenhouse gas emissions reductions at renewable energy facilities. Assessment of reductions in greenhouse gas emissions as a result of the implementation of renewable energy projects is important both for calculating the national carbon balance of the country as a whole and for accurately calculating the units of reductions planned to be issued as a result of the implementation of these projects. The Yerementau wind power plant will help the Republic of Kazakhstan in achieving the goals set ahead – increasing the share of renewable energy sources and reducing carbon dioxide emissions.Key words: renewable energy sources (RES), emission reduction, wind power, greenhouse gases, emission factor.